MYTHOLOGEME OF "EARTHLY PARADISE" IN SLAVIC BELIEFS - Матюхина, А. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to the mythologeme of "earthly paradise", the process of its changes in beliefs of the Slavic people.